Group decision support systems and group communication. - Poole, Marshall Scott; Holmes, Michael (Communication Research)
Focuses on the study that investigates a range of impacts that a computerized group decision support system (GDSS) might have on group decision-making processes. Overview of the research method; Distinct GDSS impacts on group decision making based on a review of the literature on GDSS's computer conferencing and teleconferencing; Techniques used in measuring the GDSS impact; Results of the study; Discussion of the results of the study.